PENGARUH GAYA MENGAJAR GURU TERHADAP PEMBENTUKAN KARAKTER SISWA DI SMP NEGERI 4 BATANG ANAI - Husnul Qatimah; Sara Eriza; Sz Aisyah; Khoiriah Khoiriah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Students' character development has not yet been fully optimized, as reflected in the persistence of undisciplined behavior, dishonesty, and a lack of responsibility, highlighting the need to strengthen character education in schools. Although character education has been widely investigated, empirical studies examining the influence of teachers' teaching styles on junior high school students' character development remain limited. This study aimed to analyze teachers' teaching styles, students' character development, and the influence of teachers' teaching styles on students' character development at SMP Negeri 4 Batang Anai. A quantitative correlational approach was employed involving 120 students selected through proportionate stratified random sampling. Data were collected using a validated and reliable questionnaire and analyzed using Pearson's Product-Moment correlation and simple linear regression with the assistance of SPSS. The findings revealed that both teachers' teaching styles and students' character development were categorized as good, with mean scores of 76.82 and 79.45, respectively. The correlation analysis yielded r = 0.612 with a significance value of 0.000 (p < 0.05), indicating a positive and statistically significant relationship between teachers' teaching styles and students' character development. The coefficient of determination (R² = 37.5%) indicates that teachers' teaching styles contributed substantially to students' character development. These findings suggest that democratic and interactive teaching styles can serve as effective strategies for strengthening character education and provide empirical evidence for schools to improve instructional practices that foster students' character development. ABSTRAK Karakter siswa yang belum terbentuk secara optimal, seperti rendahnya disiplin, kejujuran, dan tanggung jawab, menunjukkan pentingnya penguatan pendidikan karakter di sekolah. Meskipun pendidikan karakter telah banyak dikaji, penelitian yang menguji secara empiris pengaruh gaya mengajar guru terhadap pembentukan karakter siswa SMP masih terbatas. Penelitian ini bertujuan menganalisis gambaran gaya mengajar guru, pembentukan karakter siswa, serta pengaruh gaya mengajar guru terhadap pembentukan karakter siswa di SMP Negeri 4 Batang Anai. Penelitian menggunakan pendekatan kuantitatif korelasional dengan sampel 120 siswa yang dipilih melalui proportionate stratified random sampling. Data dikumpulkan menggunakan kuesioner yang telah dinyatakan valid dan reliabel, kemudian dianalisis dengan korelasi Product Moment dan regresi linear sederhana menggunakan SPSS. Hasil penelitian menunjukkan bahwa gaya mengajar guru dan pembentukan karakter siswa sama-sama berada pada kategori baik dengan skor rata-rata masing-masing 76,82 dan 79,45. Nilai korelasi sebesar r = 0,612 dengan signifikansi 0,000 (<0,05) menunjukkan adanya hubungan positif dan signifikan, sedangkan koefisien determinasi sebesar 37,5% menunjukkan kontribusi gaya mengajar guru terhadap pembentukan karakter siswa. Temuan ini menunjukkan bahwa penerapan gaya mengajar yang demokratis dan interaktif dapat menjadi strategi efektif untuk memperkuat pendidikan karakter serta menjadi dasar pengembangan praktik pembelajaran yang lebih berorientasi pada pembentukan karakter siswa.